Effect of auxin types on in vitro and ex vitro rooting and acclimatization of grapevine as influenced by substrates - Barreto, M. S.; Nookaraju, A. (Indian Journal of Horticulture, 2007)
Transferring micropropagated plantlets from in vitro to in vivo conditions is a critical step because plantlets have under-developed cuticle and stomata which result in wilting due to low humidity, fungal attack and bleaching in high light intensities. The resumption of terminal growth indicates successful establishment which is a change from mixotrophy to autotrophy. The survival of Vitis vinifera cvs. 2A-Clone and Red Globe plantlets rooted in vitro was 86.66 and 83.33%, respectively and the established plants showed a well-defined root system. Plantlets rooted in vivo by auxin pulse were easier to transfer and acclimatize with a survival percentage of 96.66 and 79.92 for 2A-Clone and Red Globe, respectively but the rooting was of fibrous type with few main roots and less number of root hairs. Coco-peat in combination with sand and soil was better for quick acclimatization and establishment (97.5 and 95% survival for 2A-Clone and Red Globe respectively) of the micropropagated plantlets.
Keywords: auxin pulse; coco-peat; grape; micropropagation; plantlet survival

Synergistic effect of CPPU and benzyladenine on embryo rescue in six. stenospermocarpic cultivars of grapevine - Nookaraju, A.; Barreto, M. S.; Karibasappa, G. S.; Agrawal, Dinesh C. (Vitis, 2007)
In ovulo/embryo culture technique has been used to recover hybrids from seedless grapevines. The present investigation was carried out to study the influence of pre-bloom sprays of N-(2-chloro-4-pyridyl)-N'-phenylurea (CPPU) - a synthetic cytokinin, and N-6-benzyladenine (BA) supplemented in culture media on embryo recovery in six stenospermocarpic grapevine cultivars. The results showed synergistic effect of CPPU and BA on embryo recovery. Though a CPPU spray alone increased embryo recovery in four out of six cultivars tested, the efficiency was enhanced several fold on culture of excised ovules on media supplemented with BA. The percentage of embryo recovery also depended on BA concentration and varied among six cultivars indicating a genotypic influence as well. Germination percentage of rescued embryos varied among the six cultivars and mostly corresponded with embryo recovery. Germinated embryos developed into normal plantlets. Present study demonstrates that spraying of panicles with CPPU and incorporation of BA in the ovule culture medium can enhance the embryo recovery in stenospermocarpic cultivars of grapevine.
Keywords: benzyladenine; CPPU; embryo rescue; seedless grapes

Cellular polyamines influence maturation and germination of somatic embryos from pro-embryonal masses of two grapevine cultivars - Nookapaju, A.; Barreto, M. S.; Agrawal, Dinesh C. (Vitis, 2008)
Somatic embryos of grapevine multiply repeatedly and often fail to mature and germinate due to factors like dormancy and embryo teratology. The present investigation was carried out to improve the maturation and germination of somatic embryos from pro-embryonal masses (PEM) of 2A-Clone and `Crimson Seedless', two seedless grapevine cultivars. Also, the aim was to study a correlation between cellular and residual polyamine (PA) levels in PEM and culture media. The efficiency of maturation and germination of embryos from PEM varied significantly between the two cultivars and depended on incubation period and type of PAs in the medium. HPLC analysis showed that higher levels of cellular putrescine in PEM had correlation with maturation and germination percentages in both cultivars. The levels of three PAs depleted in the media rapidly indicating its uptake by PEM. Of the three PAs, putrescine (PUT) was the most effective and resulted in 100.0 or 92.0 % maturation at 14 d or 30 d in 2A-Clone or `Crimson Seedless', respectively. The maximum germination of somatic embryos was recorded with PUT at 14 d or 21 d in 2A-Clone or `Crimson Seedless', respectively.
Keywords: germination; Grapevine; maturation; polyamines; `2A-Clone'; `Crimson Seedless'

Variability among vitis vinifera cultivars to in vitro propagation - Barreto, M. S.; Nookaraju, A.; Joglekar, A. M.; Karibasappa, G. S.; Agrawal, Dinesh C. (Proceedings of the International Symposium on Grape Production and Processing, 2008)
Response of grapevines to tissue culture has been reported to be genotype dependent, hence it becomes imperative to optimize culture conditions for newly developed varieties or cultivars, needing a large scale planting but availability of sufficient planting stock is a constraint. In the present study, conditions for in vitro propagation of six popular table grape cultivars have been standardized. Single node stem segments of cultivars 2A-Clone of Thompson Seedless, Red Globe, Crimson Seedless, Thompson Seedless, Flame Seedless and Italia cultured on ten different basal media showed varied percentages of bud break and morphogenetic responses. The percentage of bud break varied among the six cultivars. Direct rooting at basal ends of single node segments was observed in all the cultivars except in Italia. Woody plant medium induced the highest response and Eriksson medium the least in all the cultivars tested. Rooted nodal segments with shoots in axils could be established into whole plants on potting. Six cultivars showed different optimum concentrations of growth regulators for induction of maximum number of multiple shoots in both primary as well as secondary nodal segments. Shoot proliferation could be enhanced by several fold in the majority of cultivars on culture of initial shoot clumps to glass bottles instead of culture tubes. Six cultivars showed significant differences in optimum requirement of nutrients and growth regulators for shoot elongation, in vitro and ex vitro rooting and survival rate. Tissue culture plants of all the six cultivars could establish successfully in a greenhouse.
International Symposium on Grape Production and Processing, Baramati, INDIA, FEB 06-11, 2006
Keywords: basal media; Grapevine; growth regulators; micropropagation; Tissue culture; Vitis